Primary Aldosteronism and ARMC5 Variants - Zilbermint, Mihail; Xekouki, Paraskevi; Faucz, Fabio R.; Berthon, Annabel; Gkourogianni, Alexandra; Schernthaner-Reiter, Marie Helene; Batsis, Maria; Sinaii, Ninet; Quezado, Martha M.; Merino, Maria; Hodes, Aaron; Abraham, Smita B.; et al. (The journal of clinical endocrinology and metabolism, 2015)
Context:Primary aldosteronism is one of the leading causes of secondary hypertension, causing significant morbidity and mortality. A number of genetic defects have recently been identified in primary aldosteronism, whereas we identified mutations in ARMC5, a tumor-suppressor gene, in cortisol-producing primary macronodular adrenal hyperplasia.Objective:We investigated a cohort of 56 patients who were referred to the National Institutes of Health for evaluation of primary aldosteronism for ARMC5 defects.Methods:Patients underwent step-wise diagnosis, with measurement of serum aldosterone and plasma renin activity followed by imaging, saline suppression and/or oral salt loading tests, plus adrenal venous sampling. Cortisol secretion was also evaluated; unilateral or bilateral adrenalectomy was performed, if indicated. DNA, protein, and transfection studies in H295R cells were conducted by standard methods.Results:We identified 12 germline ARMC5 genetic alterations in 20 unrelated and two related individuals in our cohort (39.3%). ARMC5 sequence changes in 6 patients (10.7%) were predicted to be damaging by in silico analysis. All affected patients carrying a variant predicted to be damaging were African Americans (P = .0023).Conclusions:Germline ARMC5 variants may be associated with primary aldosteronism. Additional cohorts of patients with primary aldosteronism and metabolic syndrome, particularly African Americans, should be screened for ARMC5 sequence variants because these may underlie part of the known increased predisposition of African Americans to low renin hypertension.